Hyperbaric oxygen influences chronic wound healing - a cellular level review - Růžička, J; Dejmek, J; Bolek, L; Beneš, J; Kuncová, J (Physiological research, 2021)
Chronic wound is a serious medical issue due to its high prevalence and complications; hyperbaric oxygen therapy (HBOT) is also considered in comprehensive treatment. Clinical trials, including large meta-analyses bring inconsistent results about HBOT efficacy. This review is summarizing the possible effect of HBOT on the healing of chronic wound models at the cellular level. HBOT undoubtedly escalates the production of reactive oxygen and nitrogen radicals (ROS and RNS), which underlie both the therapeutic and toxic effects of HBOT on certain tissues. HBOT paradoxically elevates the concentration of Hypoxia inducible factor (HIF) 1 by diverting the HIF-1 degradation to pathways that are independent of the oxygen concentration. Elevated HIF-1 stimulates the production of different growth factors, boosting the healing process. HBOT supports synthesis of Heat shock proteins (HSP), which are serving as chaperones of HIF-1. HBOT has antimicrobial effect, increases the effectiveness of some antibiotics, stimulates fibroblasts growth, collagen synthesis and suppresses the activity of proteolytic enzymes like matrix metalloproteinases. All effects of HBOT were investigated on cell cultures and animal models, the limitation of their translation is discussed at the end of this review.
Keywords: hyperbarická oxygenace; výsledek terapie; Hyperbaric Oxygenation; Hypoxia-Inducible Factor 1; reaktivní formy kyslíku; reaktivní formy dusíku; Wounds and Injuries; Heat-Shock Proteins; Treatment Outcome; Reactive Oxygen Species; Animals; lidé; Wound Healing; Humans; zvířata; Reactive Nitrogen Species; faktor 1 indukovatelný hypoxií; rány a poranění; hojení ran; proteiny teplotního šoku